Rohingya Refugees and Human Security: An Analysis of Social Networks on Social Media X (Twitter) - Khairiah, Nalil; Bainus, Arry; Darmawan, Wawan Budi; Sumadinata, R. Widya Setiabudi; Santoso , Puji (Journal of Posthumanism, 2025)
The purpose of this research is (1) to explain the safety of the Rohingya people in fighting for their lives. (2) To map virtual digital opinions related to human security on Rohingya refugees on social media X. Based on the analysis of social media network X, this study seeks to investigate the complex network of public conversations surrounding the Rohingya crisis on social media platforms. Data from X We collected 2,144 Tweets. The results of this study reveal (1) the Rohingya refugee community has experienced serious discrimination and persecution in Myanmar, effectively stripping them of their citizenship. The digital public has considered the 2017 military crackdown as an ethnic cleansing campaign. (2) Social networks and discourses on Rohingya refugees in X show different characteristics, such as network characteristics, for example, fragmented, centralized, or distributed. These prominent figures in the digital arena include many key actors, such as humanitarian organizations, community leaders, journalists, and netizens.